Effects of in-center daily hemodialysis upon mineral metabolism and bone disease in end-stage renal disease patients - Lugon, Jocemir Ronaldo; André, Mauro Barros; Duarte, Maria Eugênia Leite; Rembold, Simone Martins; Cruz, Elisa de Albuquerque Sampaio da (São Paulo Medical Journal, 2001)
CONTEXT: Alternative hemodialysis schedules have been proposed to improve the quality of the dialysis. Nonetheless, their influence upon mineral and bone disorders is unknown. OBJECTIVE: To report the impact of a daily hemodialysis schedule upon the lesions of renal osteodystrophy. TYPE OF STUDY: Prospective non-controlled study. SETTING: Public University Hospital. PARTICIPANTS: Five patients treated by daily hemodialysis for at least 24 months. INTERVENTION: Daily dialysis sessions were accomplished with non-proportional dialysis machines without an ultrafiltration control device, with blood flow of 300 ml/min, bicarbonate dialysate ([Ca]=3.5 mEq/L) at 500 ml/min, and low-flux membrane dialyzers. Sessions were started at 6:00 p.m. (except Sundays) and lasted 2 hours. MAIN MEASUREMENTS: Serum levels of Ca and P from the last 6 months on conventional hemodialysis for the same patients were used for comparison with each semester of daily hemodialysis. Bone biopsies and PTH levels were obtained at the end of the conventional hemodialysis period and then again after 2 years of daily hemodialysis. RESULTS: Mean serum calcium was significantly higher during the second and third semesters of daily dialysis [10.0 mg% (SD 0.6), and 10.0 mg% (SD 0.8), respectively] compared to standard dialysis [9.4 mg% (SD 0.8)], p < 0.05. Mean values for phosphorus were significantly lower during every semester of daily hemodialysis [6.3 mg% (SD 1.8), 5.8 mg% (SD 1.7), 6.0 mg% (SD 1.7), and 6.0 mg% (SD 1.8)] compared to standard dialysis [7.2 mg% (SD 2.7)], P < 0.05. Variations in mean Ca x P product followed the same pattern as for phosphorus [59.5 (SD 16.0), 57.1 (SD 16.3), 59.8 (SD 17.7), and 58.31 (SD 20.9) vs. 68.6 (SD 27.3), P < 0.05]. After 2 years on daily hemodialysis, 2 patients who had aplastic lesion were found to have mild bone disorder. In addition, one patient with mixed bone lesion and moderate bone aluminum accumulation had osteitis fibrosa with no aluminum. Intact PTH values at the beginning of study and after 2 years on daily hemodialysis did not differ [134 pg/ml (SD 66) vs. 109 pg/ml (SD 26), P = 0.60, respectively]. CONCLUSIONS: Patients treated using daily hemodialysis had better control of serum phosphorus and perhaps a lower risk of metastatic calcifications. Daily hemodialysis also seemed to be beneficial to low turnover bone disease and bone aluminum deposition.